2005
DOI: 10.1002/jssc.200500107
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography‐mass spectrometry and related techniques for purity assessment in early drug discovery

Abstract: The combination of HPLC and MS has become the most valuable analytical tool to determine the identity and purity of a drug substance in the drug discovery arena over the past decade. This article describes different LC/MS configurations and their broad applicability to meet the fundamental analytical requirements involved in discovering new drugs. In addition, the value of chemiluminescence nitrogen detection for absolute purity determination and the convenience of CE as an orthogonal separation technique to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…While in the development stage a limited number of samples are analyzed in significant detail, scientists in the discovery stage are faced with the need to provide purity assessment for thousands of compounds on a monthly, if not weekly, basis [59,60]. In addition, impurity profiling in drug development is mainly a tool to understand and above all gain control over the production process and in addition to prove the safety of the total product.…”
Section: Purity Analysis and Impurity Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…While in the development stage a limited number of samples are analyzed in significant detail, scientists in the discovery stage are faced with the need to provide purity assessment for thousands of compounds on a monthly, if not weekly, basis [59,60]. In addition, impurity profiling in drug development is mainly a tool to understand and above all gain control over the production process and in addition to prove the safety of the total product.…”
Section: Purity Analysis and Impurity Profilingmentioning
confidence: 99%
“…An exact reproduction of the impurity profile of the various "discovery batches" is of lesser importance; in case of unexplained findings, the identity of impurities can be requested. In contrast to the drug development stages, the large diversity in chemical structures and structural properties, in combination with the required short analysis times, has led to the introduction of more "generic" high-throughput HPlC-uV-MS platforms for this purpose [60]. While HPlC-uV-MS has become very useful for drug purity screening, there are some practical considerations that should be understood.…”
Section: Purity Analysis and Impurity Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…However purity requirements and analytical procedures differ according to the drug discovery stage from chemical synthesis to compound selection for development (2,3). Whereas in later stages of pharmaceutical development, individually validated methods for each active pharmaceutical ingredient (API) are necessary and required by regulators, such an approach is not practical in earlier stages of discovery and generic methods applicable to a range of compounds must be used to deliver acceptable analysis rates.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that the use of orthogonal separation procedures reduces the risk of incorrect purity assessment of drug compounds and ensures the quality and safety of drug products. This can be achieved by changing pH, organic solvents, aqueous buffer and stationary phases [13][14][15][16]. Several elegant approaches have been used to automate this method searching.…”
Section: Introductionmentioning
confidence: 99%